Effect of Neem Seed Kernel Extracts on Spermoplane Fungi of Neem (Azadirachta indica) Seed - Srivastava, K. K.; Gupta, P. K.; Mishra, D. K. (Indian Forester, 1998)
Effect of three isolates from Neem Seed Kernel Powder (NSKP) was studied on the seeds of Azadirachta indica A. Juss. (Neem) collected from both viz., summer (stored at ambient and low temperature) and winter fruiting seasons. Significant effect of various extracts was noticed even at 0.2 per cent concentration. However, methanol and water soluble extracts showed better results than MeOH-water extract against spermoplane fungi of Neem seed.